2014
DOI: 10.1186/1471-2458-14-507
|View full text |Cite
|
Sign up to set email alerts
|

HIV behavioural interventions targeted towards older adults: a systematic review

Abstract: BackgroundThe increasing number of people living with HIV aged 50 years and older has been recognised around the world yet non-pharmacologic HIV behavioural and cognitive interventions specifically targeted to older adults are limited. Evidence is needed to guide the response to this affected group.MethodsWe conducted a systematic review of the available published literature in MEDLINE, Embase and the Education Resources Information Center. A search strategy was defined with high sensitivity but low specificit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
38
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
7
3

Relationship

1
9

Authors

Journals

citations
Cited by 43 publications
(43 citation statements)
references
References 64 publications
(78 reference statements)
3
38
1
Order By: Relevance
“…47,48 Specific programs ensuring universal HIV testing, rapid linkage of HIV-positive people to care, and supported HIV treatment retention and adherence should also be considered. 17,49 Among HIV-negative older adults, it will be important to consider how established interventions, such as medical male circumcision 50 and condom promotion, and novel interventions, such as preexposure prophylaxis, 18 can be designed and delivered in ways that best meet the needs of older adults. 46,49 In general, it is likely that to reach older adults with HIV prevention messages, interventions will need to explore disseminating messages through different channels than have been successfully used for younger age groups (ie, social media and social venues).…”
Section: Discussionmentioning
confidence: 99%
“…47,48 Specific programs ensuring universal HIV testing, rapid linkage of HIV-positive people to care, and supported HIV treatment retention and adherence should also be considered. 17,49 Among HIV-negative older adults, it will be important to consider how established interventions, such as medical male circumcision 50 and condom promotion, and novel interventions, such as preexposure prophylaxis, 18 can be designed and delivered in ways that best meet the needs of older adults. 46,49 In general, it is likely that to reach older adults with HIV prevention messages, interventions will need to explore disseminating messages through different channels than have been successfully used for younger age groups (ie, social media and social venues).…”
Section: Discussionmentioning
confidence: 99%
“…Studies have shown that increasing the knowledge of HIV can significantly reduce the risk of HIV transmission (15, 18, 23). The potential of behavioral intervention in curbing HIV-risk behaviors has been underscored by many researchers (21, 24, 25). A major challenge for behavioral intervention is that it cannot address the underlying condition of poverty, which is an important risk factor for poor health, low literacy, and overall socioeconomic well-being (26, 27).…”
Section: Introductionmentioning
confidence: 99%
“…This increase in HIV diagnoses in older females could be partly due to older women being less concerned with the risks of pregnancy and, therefore maybe more likely to engage in unprotected sex (22, [26][27][28]. The observed increase in annually reported HIV diagnoses may also be attributed in part to previous positive HIV diagnoses, where a person may be tested and reported as a new diagnosis more than once due to inter-provincial migration or migration into Canada after a HIV diagnosis outside of Canada.…”
Section: Discussionmentioning
confidence: 99%